Sing a Song of Sixpence - Randall, Ronne; Dodd, Emma (London Ladybird, 2008)
Offers an introduction to the nursery rhyme, Sing a Song of Sixpence. This book helps young children to hear the rhyme, look at the pictures and feel the different textures
Rymes and Songs
1 2 13 18 22 23
Keywords: English poetry